Evolution of Co-Operative Movement in Haryana: A Brief Study: Addressing Unemployment through Co-operative Movement in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2018)
To give momentum of the co-operative movement in Haryana, the Governing Act i.e. Punjab State Co-operative Act, 1961 and Punjab Agriculture Development Act, 1957 which lacked in several supporting provisions were replaced and the new co-operative societies Act, 1984 was put into force. Co-operative movement in Haryana has been undertaking need-based programmes however challenging they may be recently co-operative sector has embarked upon a programme for providing self-employment opportunities to unemployed youth. The co-operative credit system primarily responsible for providing credit for agriculture and allied activities has also started financing non-agricultural activities including service sector. The minimum membership for formulation of any co-operative society is 10 but with the amendments made in year 1997, The State Government has decide to offer bus-route permits on link roads to transport co-operative societies and has amended co-operative societies act to reduce the minimum membership of these societies to five only for transport societies. Co-operative banks have geared up to finance these societies in a big way to meet the challenges of unemployment in the state.